(untitled) (Journal of Plant Disease Sciences, 2017)
Fenugreek (Trigonella foenum graecum L.) is affected by many diseases; downy mildew caused by Peronospora trigonella Gaum is considered one of the most destructive and wide spread diseases of the crop, which is commonly occurring February and March (Thind, 1942, Gupta ., 2015). et al The infected leaves are easily detected by the presence of yellow patches on the upper surface and cottony grayish- violet mycelial growth on the lower surface of the leaves. The disease is also reported from Algeria, Pakistan, United Kingdom and India (Acharya, 2014). The common methods of disease managements are use of chemical and disease resistant variety. However continuous use of chemicals to control plant diseases is neither environmentally sound nor economically cheap (Iqbal , 2011). The et al. literature on downy mildew resistant germplasm of fenugreek is scanty. Therefore identification of downy mildew resistant / tolerant genotypes of the self pollinated crop will be useful for development of resistant cultivars where the disease is prevalent and causing heavy yield loss.